Detection of Plasmodium knowlesi, Plasmodium falciparum and Plasmodium vivax using loop-mediated isothermal amplification (LAMP) in a co-endemic area in Malaysia. (December 2017) - Piera, Kim; Aziz, Ammar; William, Timothy; Bell, David; González, Iveth; Barber, Bridget; Anstey, Nicholas; Grigg, Matthew
Abstract Background Plasmodium knowlesi is the most common cause of malaria in Malaysia. However, microscopic diagnosis is inaccurate and rapid diagnostic tests (RDTs) are insufficiently sensitive. PCR is sensitive and specific but not feasible at a district level. Loop-mediated isothermal amplification (LAMP) shows potential with only basic requirements. A commercially available LAMP assay, the Eiken Loopamp™ MALARIA Pan Detection kit, is sensitive forPlasmodium falciparum andPlasmodium vivax, but has not previously been evaluated forP. knowlesi . This study aims to determine the sensitivity of this LAMP assay for detectingP. knowlesi infection. Methods Study participants included 73 uncomplicated malaria patients with PCR species confirmation: 50P. knowlesi, 20P. falciparum and 3P. vivax . Nineteen malaria-negative, non-endemic area controls were also included. The sensitivity of the Eiken Loopamp™ MALARIA Pan Detection kit (Pan LAMP) for detecting eachPlasmodium species was evaluated. Sensitivity and specificity of the Eiken Loopamp™ MALARIAPf Detection kit (Pf LAMP) forP. falciparum were also determined. The limit of detection for each LAMP assay was evaluated, with results compared to PCR. AllP. knowlesi patients were also tested by CareStart™ (Pf/VOM) and OptiMAL-IT™ (Pan/Pf) RDTs. Results The sensitivity of the Pan LAMP assay was 100% forP. knowlesi (95% CI 92.9–100), P. falciparum (95% CI 83.2–100), andP. vivax (95% CI 29.2–100). ThePf LAMP was 100% sensitive and specific forP. falciparum detection, with allP. knowlesi samples having a negative reaction. LAMP sensitivity was superior to both RDTs, with only 10 and 28% ofP. knowlesi samples testing positive to CareStart™ and OptiMAL-IT™, respectively. Limit of detection using the Pan LAMP for bothP. knowlesi andP. vivax was 2 parasites/μL, comparable to PCR. ForP. falciparum both the Pan LAMP andPf LAMP demonstrated a limit of detection of 20 parasites/μL. Conclusions The Eiken Loopamp™ MALARIA Pan Detection kit is sensitive for detection ofP. knowlesi in low parasitaemia clinical infections, as well asP. falciparum andP. vivax. However, aP. knowlesi -specific field assay in a simpler format would assist correct species identification and initiation of optimal treatment for all malaria patients.